Deconstruction of the ultimum remedium basic concept on protection and management tropical biodiversity. Issue 1 (November 2021) - Dewi, D K; Syahrin, A; Suhaidi; Ekaputra, M; Putra, T A D
Abstract: The biological potential in Indonesia is no longer managed and protected. So far Indonesia has had biologically related laws and regulations, but its implementation is still weak and less effective. Therefore, Law No. 32 of 2009 on Environmental Protection and Management or called UUPPLH mentioned the management and protection of biodiversity based UUPPLH namely two principles in law of criminal provision, the principle of remedium ultimum which is an effort, and the principle of premium remedium that takes care of the law. So far many mistakes in interpreting the application of the principle of remedium ultimum which is said to make it difficult for law enforcement to enforce environmental criminal laws and can shackle law enforcements in carrying out task of environmental law enforcement. In addition, it is also said that the principle of remedium ultimum can also harm the environment due to violations of waste water quality standards, emissions, and disturbances that take precedence is the administration of administrative sanctions, meaning that there is no deterrent effect on perpetrators. Therefore, it is necessary to deconstruct the principle of remedium ultimum in the proper enforcement of environmental criminal law including structuring and enforcement (compliance) which can also be a view of criminal law that can be used as an instrument in the framework of protection and management of tropical biodiversity, especially the environment and can bring consequences for the intertwining of criminal law with administrative law. The results of the research are based on UUPPLH that can protect biodiversity by Indonesia and reconstruct the principle of ultimum remedium in environmental law. Research methods using normative legal research on philosophical.